Implementation of measures for minimization of environmental impact and preservation of public health at modern domestic sugar-refineries within the directives 2008/50 / EU - Makhniuk, V.M.; Pelekh, L.V.; Melnychenko, S.O.; Honcharuk, V.S. (Environment & Health, 2019)
Objective: Hygienic assessment of the implementation of the measures for the decrease of ambient air pollution at the modern domestic sugar-refineries and developed sanitary–and-hygienic requirements for the minimization of the impact of thye negative consequences of their operation on the environment and public health.Materials and methods: We used the following methods in the study: bibliosemantic (for the analysis of the application of standard-and-legal regula-tion), theoretical (retrospective use of the data of the scientific research), analytical, and sanitary-and-hygienic examination of design materials.Results: In this article, the design materials of existing sugar-refineries with the different technologies of the industrial waste handling, in particular with raw pulp, were analyzed. The sugar-refineries, including the pulp pits for the storage of wet pulp in its production, were chosen for the study. For comparison with the traditional production technologies, research was carried out at a sugar-refinery with a new pulp drying technology. According to the results of the research, the liquidation of pulp pits and the transfer to a new pulp drying technology reduces the technogenic load on the environment and minimizes the impact of the consequences of the enterprise’s operation on the public health of the adjacent residential building which complies with the requirements of the current domestic normative documents and the requirements of Directive 2008/50 / EU.Conclusions:1. Implementation of the measures for the minimization of the environmental impact of the sugar-refinery No. 3 with the latest technologies (pulp drying, pulp granulation department) in comparison with the sugar-refineries No.1 and No.2 with traditional production technologies ensures a decrease of atmospheric air pollution and meets the requirements of existing SSR No. 173-96 and Directive 2008/50 / EC according to the following criteria:2. Designed maximum surface concentrations of the pollutants at the border of the new normative SPZ of 100 m for the sugar-refinery № 3 with the modernized production technology corresponded to the current domestic "State Sanitary Regulations for Planning and Development of the Settlements. SSR No. 173-96 " (p. 5.4) and "List of Maximum Allowable Concentrations of Chemical and Biological Substances in the Atmospheric Air of the Settlements " and the Directive 2008/50 / EU of the European Parliament and of the Council for the Ambient Air Quality and Cleaner Air for Europe, 21 May 2008.
Keywords: EU directive; measures to minimize the environmental impact; sanitary-and-hygienic requirements; public health; sugar-refineries with a new sugar production technology